2007
DOI: 10.1002/app.26590
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of poly(lactic acid) and pectin composite films intended for applications in antimicrobial packaging

Abstract: A pectin and poly(lactic acid) (PLA) composite was compounded by extrusion. A model antimicrobial polypeptide, nisin, was loaded into the composite by diffusion. The incorporation of pectin into PLA resulted in a heterogeneous biphasic structure, as revealed by scanning electronic microscopy, confocal laser microscopy, and fracture-acoustic emission. The incorporation of pectin also created a rough and cragged surface, which was hydrophilic and facilitated the access and absorption of nisin. The nisin-loaded c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
2
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(62 citation statements)
references
References 35 publications
4
54
2
2
Order By: Relevance
“…They have been used in many industrial applications, such as in packaging, coating or protective films for the shipping and handling of different materials, [1][2][3] and controlled delivery of drugs. 4,5 They are also used for their pharmacological activity. [6][7][8] Alginate is a linear polysaccharide derived from brown sea algae and is composed of (1→4)-linked b-D-mannuronate residues (M units) and (1→4)-linked a-Lguluronate (G units) in different proportions.…”
Section: Introductionmentioning
confidence: 99%
“…They have been used in many industrial applications, such as in packaging, coating or protective films for the shipping and handling of different materials, [1][2][3] and controlled delivery of drugs. 4,5 They are also used for their pharmacological activity. [6][7][8] Alginate is a linear polysaccharide derived from brown sea algae and is composed of (1→4)-linked b-D-mannuronate residues (M units) and (1→4)-linked a-Lguluronate (G units) in different proportions.…”
Section: Introductionmentioning
confidence: 99%
“…PLA (poly(D/L-lactic acid) in combination with pectin (Liu et al, 2007) or alginate (Jin et al, 2009) had been shown as effective antimicrobial packaging material. Theinsathid et al (2012) reported antilisterial and antisalmonellal activity of PLA films coated with lauric arginate for use in food-contact packaging of cooked sliced ham to combat foodborne pathogens.…”
Section: Release Of Sl From Biopolymersmentioning
confidence: 99%
“…However, it has been found that the above drawbacks can be overcome by the addition of an appropriate filler (7)(8)(9)(10)(11)(12)(13)(14). Many studies have been conducted to provide PLA with antimicrobial properties that might encourage its use in active food packaging as well as in specific biomedical applications (15)(16)(17)(18)(19)(20). Controlled drug delivery systems are attracting increasing attention in the biomedical and pharmaceutical sectors (21)(22).…”
Section: Introductionmentioning
confidence: 99%